2016
DOI: 10.1182/blood-2015-05-647560
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanics of clot contraction are governed by the molecular and cellular composition of the blood

Abstract: Key Points Clot contraction has 3 phases differentially affected by platelet and fibrin mechanics, RBC compaction, and various blood components. A new dynamic quantitative clot contraction assay can reveal novel aspects of formation and evolution of hemostatic clots and thrombi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
222
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 145 publications
(252 citation statements)
references
References 53 publications
21
222
1
8
Order By: Relevance
“…Additionally, we are able to visualize the structure of polyhedrocytes within the clot volume. Our results show significant impairment of clot contraction in the presence of blebbistatin, confirming previous findings indicating an important role for actomyosin in platelet-driven clot contraction [32].…”
Section: Application Of Cclot Methods To Human Bloodsupporting
confidence: 82%
“…Additionally, we are able to visualize the structure of polyhedrocytes within the clot volume. Our results show significant impairment of clot contraction in the presence of blebbistatin, confirming previous findings indicating an important role for actomyosin in platelet-driven clot contraction [32].…”
Section: Application Of Cclot Methods To Human Bloodsupporting
confidence: 82%
“…Sample clot sizes were then tracked using a Thrombodynamics Analyzer System (HemaCore, Moscow, Russia) by accumulating digitized images based on the light-scattering properties of the clot every 15 s for 20 min (24). Measuring contractile stress in constrained clot contraction…”
Section: Measuring the Kinetics Of Unconstrained Clot Contractionmentioning
confidence: 99%
“…It is possible to theoretically understand the origin of the macroscopic viscoelastic properties of the blood clot by modeling the biopolymer as a semiflexible polymer network (20)(21)(22). The incorporation of RBCs into the blood clot volume disrupts the uniformity of the fibrin network (23), affects the mechanical properties of the clot (24), and influences the process of clot contraction (24). RBCs are easily deformed (25), and when subjected to compressive forces such as those generated by contracting platelets, they become packed in the core of the blood clot and take on a polyhedral shape (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have suggested platelet FXIII is essential for platelet contraction(45), we and others have detected only moderate or no influence of platelet FXIII on platelet contractile events. (31, 46, 47)…”
Section: Fibrin Formation Structure and Function In Vtmentioning
confidence: 99%